The therapist’s perspective of parental involvement in applied behavioural analysis (ABA) therapy for children with autism spectrum disorder (ASD) - Choo, Alisa Ai Ling; Ching, Sin Siau; Mimi Fitriana,; Clarisse Roswini Kalaman,; Lee, Sook Huey (Penerbit Universiti Kebangsaan Malaysia, 2022)
ABA interventions have been widely known as the most effective evidence-based interventions for children with ASD. Parents have been reported as a critical component that impacts ABA treatment outcomes in the long term. However, many parents still do not partake in ABA treatment as recommended or end up dropping out before behavioural issues are resolved. This study aims to understand ABA therapists’ perception on parental involvement, perceived level of involvement, and factors leading to involvement. Five ABA therapists in Malaysia were recruited for the purpose of this study. A semi-structured interview method was used, and thematic analysis was utilized to code the data. The themes identified for perceived parental involvement include active interaction between parents and therapist, engagement with the ASD child, behavioural observation of the ASD child, commitment to attend ABA parent training, compliance with the ABA teaching at home, and adjustment of parental behaviours that interferes with therapy. Differing perceptions on the level of parental involvement were found. Parental stress level, involvement from fathers, parents’ career, ASD severity level, parents’ efficacy and accessibility to a therapist are factors perceived to be related to parental involvement. A greater focus on how to improve parental involvement could be beneficial for the therapist, parents, and the child him/herself.